Are consumers more sensitive to price changes during food scares? A regime-switching dynamic almost ideal demand system approach - Yan Jin; José María Gil (Agricultural and Food Economics)
Abstract Using a regime-switching dynamic Almost Ideal Demand System, this study investigates the change in consumer behavior during the tuna scare in Spain. The scare was caused by a histamine outbreak in 2017 that resulted from inadequate temperature in storage and color modification. To measure consumer awareness of the scare, we developed a communication index based on the number of relevant Twitter (now rebranded as X) posts regarding the safety of tuna consumption and used its magnitude to identify the high and low communication regimes. Using Marshallian price elasticity and expenditure elasticity as indicators, we analyzed the change in consumer behavior during the scare. In the high communication regime, consumers became significantly less sensitive to tuna prices but significantly more sensitive to the prices of salmon and hake. With a hypothetical increase in fish expenditure, a representative consumer would reallocate their budget by decreasing their share of tuna, hake, and other fishes while increasing their share of salmon. The change in consumer behavior started as soon as the communication on Twitter commenced, and it lasted for 10 days. This paper concludes with implications for risk communication and management during a mild food scare.